2022
DOI: 10.1002/jcla.24267
|View full text |Cite
|
Sign up to set email alerts
|

PBMC CDC42 reveals the disease activity and treatment efficacy of TNF inhibitor in patients with ankylosing spondylitis

Abstract: Objective Cell division cycle 42 (CDC42) regulates the polarization of M2 macrophage and maintains the T cell homeostasis, to participate in multiple autoimmune diseases, while its clinical involvement in ankylosing spondylitis (AS) remains unclear. Hence, the current study aimed to investigate the correlation of CDC42 with clinical characteristics and treatment outcome in AS patients receiving tumor necrosis factor (TNF) inhibitor therapy. Methods Peripheral blood mononuclear cell (PBMC) CDC42 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…CDC42 is previously reported to be associated with etanercept response in AS patients, while the correlation of CDC42 with IFX response in UC patients has not been determined. 17 Then, CDC42 at W0 and W12 was detected in the current study aiming to observe its longitudinal change during IFX treatment, and it was observed that CDC42 was elevated during IFX treatment in active UC patients.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…CDC42 is previously reported to be associated with etanercept response in AS patients, while the correlation of CDC42 with IFX response in UC patients has not been determined. 17 Then, CDC42 at W0 and W12 was detected in the current study aiming to observe its longitudinal change during IFX treatment, and it was observed that CDC42 was elevated during IFX treatment in active UC patients.…”
Section: Discussionmentioning
confidence: 79%
“…For instance, CDC42 is reduced in AS patients, RA patients, and pediatric CD patients compared with controls. [16][17][18] Also, CDC42 is related to a lower risk of active CD in children, 18 while the clinical value of CDC42 in UC patients remains exclusive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations